2017
DOI: 10.1038/cddis.2017.300
|View full text |Cite
|
Sign up to set email alerts
|

miR-181d and c-myc-mediated inhibition of CRY2 and FBXL3 reprograms metabolism in colorectal cancer

Abstract: Colorectal cancer (CRC) is the second major cause of tumor-related deaths. MicroRNAs (miRNAs) have pivotal roles in CRC progression. Here, we describe the effect of miR-181d on CRC cell metabolism and underlying molecular mechanism. Our data firmly demonstrated that knockdown of miR-181d suppressed CRC cell proliferation, migration, and invasion by impairing glycolysis. Mechanistically, miR-181d stabilized c-myc through directly targeting the 3′-UTRs of CRY2 and FBXL3, which subsequently increased the glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 26 publications
3
39
1
Order By: Relevance
“…Our study provided evidence that CRY1 is indeed a target gene of miR-181a and that the elevation of miR-181a could lead to the direct down-regulation of CRY1. Moreover, miR-181d expression can also directly target the 3’-UTRs of CRY2 and FBXL3, providing information on its association with colorectal cancer (Guo et al 2017 ). Our results and others’ lead to the conclusion that an increased expression of miR-181a results in the down-regulation of CRY1, in turn promoting the GS and RTE injury in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Our study provided evidence that CRY1 is indeed a target gene of miR-181a and that the elevation of miR-181a could lead to the direct down-regulation of CRY1. Moreover, miR-181d expression can also directly target the 3’-UTRs of CRY2 and FBXL3, providing information on its association with colorectal cancer (Guo et al 2017 ). Our results and others’ lead to the conclusion that an increased expression of miR-181a results in the down-regulation of CRY1, in turn promoting the GS and RTE injury in CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Na et al [83] demonstrated that miR-181d and miR-191 exhibited inversely correlated circadian rhythm by controlling the circadian initiators, clock and Bmal1 in mouse liver [83]. In colorectal cancer, miR-181d plays an oncogenic role by directly targeting the 3 -UTRs of CRY2 and FBXL3 and by promoting glycolysis which implies the notion that dysregulated expression of clock gene leads the formation of tumor [84,85]. Cancer progression is also influenced by the circadian system whose functioning is based on the rhythmic expression of clock genes.…”
Section: Role Of Micrornas In Molecular Clock Regulation: Implicationmentioning
confidence: 99%
“…The majority of the remaining previously reported genes in pCRC are the MIR-15 family member, Mir-29-P2a/b ( miR-29b ), two MIR-96 family members, Mir-135-P3, Mir-130-P2a ( miR-301a ) [41,42] , Mir-181-P1c [43] , and Mir-224 [18,39] . Mir-95-P2…”
Section: Pcrc Signature Mirnasmentioning
confidence: 99%